Implementasi Pemberdayaan Masyarakat dalam Program Keluarga Harapan untuk Memutus Rantai Kemiskinan di Kota Malang: Studi di Kecamatan Lowokwaru Kota Malang - Arif Citra Permana; Cahyo Sasmito; Cakti Indra Gunawan (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2018)
Family Hope program is a program to break the chains of poverty. Malang received it the year 2013. Community empowerment in the PKH step acceleration for poverty reduction. This research aims to analyze (1) implementation of community empowerment, (2) factor endowments and a barrier, and (3) the impact of the implementation of community empowerment in the family Program Hopes to break the chains of poverty in Sub Lowokwaru Malang. The research was conducted using qualitative methods. Based on research it was concluded that the implementation of empowerment in the implementation of the Program of family Expectations are improving the quality of life of participants PKH by improving family health and educational aspects, the active role of the participants PKH in this program, the national program and the involvement of the participants in the PKH socialization thing – a good thing to the surrounding community. Supporting factors, namely the existence of a companion PKH, liveliness of local government as well as the willingness of community participants of this program to get better. While the factor penghambatnya is a program in terms of the rule of unpreparedness and the readiness of the program stakeholders. The impact of the implementation can be seen in improving the status of the health, education and welfare of the Family Hope Program participants in the city of Malang.